Chiropractic spinal manipulation alters TMS induced I-wave excitability and shortens the cortical silent period. (October 2018) - Haavik, Heidi; Niazi, Imran Khan; Jochumsen, Mads; Uginčius, Paulius; Sebik, Oğuz; Yılmaz, Gizem; Navid, Muhammad Samran; Özyurt, Mustafa Görkem; Türker, Kemal S.
Abstract: The objective of this study was to construct peristimulus time histogram (PSTH) and peristimulus frequencygram (PSF) using single motor unit recordings to further characterize the previously documented immediate sensorimotor effects of spinal manipulation. Single pulse transcranial magnetic stimulation (TMS) via a double cone coil over the tibialis anterior (TA) motor area during weak isometric dorsiflexion of the foot was used on two different days in random order; pre/post spinal manipulation (in eighteen subjects) and pre/post a control (in twelve subjects) condition. TA electromyography (EMG) was recorded with surface and intramuscular fine wire electrodes. Three subjects also received sham double cone coil TMS pre and post a spinal manipulation intervention. From the averaged surface EMG data cortical silent periods (CSP) were constructed and analysed. Twenty-one single motor units were identified for the spinal manipulation intervention and twelve single motor units were identified for the control intervention. Following spinal manipulations there was a shortening of the silent period and an increase in the single unit I-wave amplitude. No changes were observed following the control condition. The results provide evidence that spinal manipulation reduces the TMS-induced cortical silent period and increases low threshold motoneurone excitability in the lower limb muscle. These finding may have important clinical implications as they provide support that spinal manipulation can be used to strengthen muscles. This could be followed up on populations that have reduced muscle strength, such as stroke victims.